Buckling of carbon-fibre reinforced polymer composites perforated plates subjected to shear loading - Osman, Iman Syahirah (2022)
Buckling occurs when composite laminated plates are forced into shear or compression. Composite materials combine two or more components to minimize weight while preserving strength and less attention has been paid to composite plate buckling. In order to develop more efficient and lighter structures, holes are frequently required. Also, to improve reliability and performance, these structural components must be analysed with various hole shapes under in-plane loads such as shear. Although research has been done on the effect of cutouts on plate structure, little is known about shear loading on symmetrical angle plied square plates with center cutouts. As a result, the current study used a circular hole in the center of the plate with angle ply stacking and shear loading as well as to evaluate the influence of shear load directions on the behavior of symmetric angle ply CFRP laminates. To achieve the study's objectives, an understanding of laminated square plate buckling is required, particularly under shear loads. The current work analysis is completely numerical, using FEA software. This method has been studied for use in the current study since it can save time and cost. Since the current study uses ABAQUS to complete the analysis, the method for using the software is obtained. The results of the numerical analysis are compared to previously available theoretical data gathered through a literature study. The percentage difference used in this study must be less than 10% to be legitimate and accepted. Carbonfiber reinforced polymers (CFRP) were chosen for the current investigation due to their material properties and common application in aerospace. This work's basic model geometry is a 200mm x 200mm square plate with no cutout. The model's central section is removed to further investigate shear buckling behavior of laminated square plates. The type of hole analysed is circular to guarantee consistency. The hole diameter/width ratio, d/b on perforated plates can affect the shear buckling behavior of square perforated plates. As the hole ratio d/b increases, the plate's strength decreases. The study's findings showed that composite structural parts with plate holes require special consideration. They have variable buckling capabilities depending on the shear stress and the holes. The perforated plate with a hole d/b of 0.5 exhibits the greatest decrease in critical buckling stresses, whereas the perforated plate with a hole d/b of 0.1 exhibits the least reduction in critical buckling stresses. Additionally, the results of the analysis of plates with cutouts subjected to shear loadings can be used to guide researchers and engineers in determining the size of the hole that can be generated in their plate structure designs, notably in finite element analysis.